2009
DOI: 10.1002/jclp.20629
|View full text |Cite
|
Sign up to set email alerts
|

Major and minor depression in female adolescents: onset, course, symptom presentation, and demographic associations

Abstract: We examined the epidemiology and phenomenology of major depressive disorder (MDD) and minor depression among a community sample of 496 female adolescents. Diagnostic interviews were conducted annually for 7 years, allowing us to examine onset, course, and symptom presentation among participants 12 through 20 years old. Approximately 1 of 6 girls experienced MDD. MDD episodes had a mean duration of 5.3 months (SD = 4.2). One-year prevalence for MDD peaked at age 16 (5.3%). White racial status and younger age we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 16 publications
2
74
2
Order By: Relevance
“…Thus, according to our results, one-third of the sample would be at risk for a depressive syndrome or, at least, mild symptoms of depression. Although a similar prevalence of depressive symptoms has been detected in other investigations 25,28,34,35 , our results differ significantly from previous reports in the literature regarding the diagnosis of major depression in the adolescent population (ranging from 0.4% to 8.3%) 23,36 . A possible explanation for the increased depression rates in our sample could be the fact that the rating scales were more likely to estimate general psychiatric symptoms rather than depression itself.…”
Section: Discussioncontrasting
confidence: 92%
“…Thus, according to our results, one-third of the sample would be at risk for a depressive syndrome or, at least, mild symptoms of depression. Although a similar prevalence of depressive symptoms has been detected in other investigations 25,28,34,35 , our results differ significantly from previous reports in the literature regarding the diagnosis of major depression in the adolescent population (ranging from 0.4% to 8.3%) 23,36 . A possible explanation for the increased depression rates in our sample could be the fact that the rating scales were more likely to estimate general psychiatric symptoms rather than depression itself.…”
Section: Discussioncontrasting
confidence: 92%
“…Still, studies of late adolescence Fergusson et al, 2005;Shankman et al, 2009;Lewinsohn et al, 2000) produce results similar to the adult studies, and population-based taxometric analyses suggest that depression may be viewed dimensionally also in children and adolescents (Hankin et al, 2005). Recent studies suggest that childhood and adolescent SD is associated with severe impairment (Keenan et al, 2008;Gonzalez-Tejera et al, 2005), and with future risk of developing MDD (Rohde et al, 2009;Johnson et al, 2009) similar to findings in adult populations. Hence, if SD in children and adolescents is a precursor to MDD, it would be an obvious target for indicated preventive intervention (aimed at individuals with subthreshold symptoms) (Munoz et al, 2010).…”
Section: Introductionmentioning
confidence: 73%
“…It has been suggested that middle-to-late adolescence (15-18 years) may be a critical time for studying vulnerability to depression as there is greater risk for depression onset during this period. A dramatic increase in gender differences in depression has been observed in this group also, young women being more affected (Hankin et al 1998;Rohde et al 2009). All the above mentioned risk factors are associated with stress, hence, an understanding of stress is also essential in the present context.…”
Section: Bipolar Depressionmentioning
confidence: 94%